Ecology of top fish predators, European catfish and asp, with consequences to fish communities - Šmejkal, Marek (Jihočeská univerzita, 2017)
The dissertation thesis focuses on predator ecology in artificial water bodies. Paper I deals with the importance of chemical cues for predator-prey interactions in an aquatic environment. Here, I demonstrate that the ability to detect chemical cues represents a survival benefit for prey species. Paper II points out gillnet methodological bias, which may have subsequent repercussions in field evaluation of a predator's presence and assessment of larger fish abundance in general. Papers III and IV focus on asp Leuciscus aspius spawning grounds. In Paper III, I demonstrate how males maximize their spawning chances by early arrival and in Paper IV, I evaluate the predation pressure of asp prey, Alburnus alburnus, directed on asp eggs.
Ecology of top fish predators, European catfish and asp, with consequences to fish communities
Keywords: chemical cues; European catfish; asp; bleak; protandry; predator-prey reversal; chemical cues; European catfish; asp; bleak; protandry; predator-prey reversal